2012
DOI: 10.1167/iovs.11-8836
|View full text |Cite
|
Sign up to set email alerts
|

Repeatability and Reproducibility of Subfoveal Choroidal Thickness in Normal Eyes of Japanese Using Different SD-OCT Devices

Abstract: SCT measurements obtained with three different SD-OCTs were highly correlated and could be used interchangeably. (http://upload.umin.ac.jp number, UMIN000005287.).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
93
3
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 147 publications
(108 citation statements)
references
References 27 publications
10
93
3
1
Order By: Relevance
“…Mean value ± standard deviation was -3.87±22.06µm, higher than the value previously reported by Rahman et al 31 but of the same order of magnitude. subfoveal choroidal thickness was the only comparable value, owing to the different methods used to acquire images.Yamashita et al 32 reported nasal, subfoveal and temporal ICC values of 0.978, 0.976 and 0.904, respectively, similar to our results. The authors calculated subfoveal and temporal COVs of 23%, with a nasal value of 27%.…”
supporting
confidence: 91%
See 1 more Smart Citation
“…Mean value ± standard deviation was -3.87±22.06µm, higher than the value previously reported by Rahman et al 31 but of the same order of magnitude. subfoveal choroidal thickness was the only comparable value, owing to the different methods used to acquire images.Yamashita et al 32 reported nasal, subfoveal and temporal ICC values of 0.978, 0.976 and 0.904, respectively, similar to our results. The authors calculated subfoveal and temporal COVs of 23%, with a nasal value of 27%.…”
supporting
confidence: 91%
“…Yamashita et al 32 reported nasal, subfoveal and temporal ICC values of 0.978, 0.976 and 0.904, respectively, similar to our results. The authors calculated subfoveal and temporal COVs of 23%, with a nasal value of 27%.…”
supporting
confidence: 91%
“…Previous studies also showed that the measurements of choroidal thickness, using EDI-OCT, have good reproducibility and repeatability. 25,26 Besides, considering the similarity of the normal values of this study and that of the previous studies, measuring error may not be significant. 10,26,27 In conclusion, increased SFCT of patients with CSC was reduced after spontaneous resolution and lowfluence PDT.…”
Section: Discussionsupporting
confidence: 61%
“…Previous studies excluded eyes with indistinct CSI or extrapolated the CSI. 18,19 Although exclusion of eyes with an indefinite boundary could result in higher repeatability, it might not reflect the practical aspects and cause selection bias. Hence, the current study adopted the extrapolation method, because the indistinct CSI should be considered a significant factor in measurement error.…”
Section: Discussionmentioning
confidence: 99%
“…Two previous investigations revealed high reliability and a strong correlation when comparing repeatability after scanning with three different SD-OCT devices. 18,19 Yamashita et al, 18 however, only considered eyes for which a distinct choroid boundary was seen by both observers, and Branchini et al 19 also averaged the measurements of two observers. Consequently, their studies had a greater tendency to overestimate repeatability than ours.…”
Section: Eyementioning
confidence: 99%